The First Step of the Project for the Interaction of an Open Data Platform with an Intersectional Feminist Lens - Lima, Patrícia Raposo Santana (2023)
The Feminist HCI is characterized as the integration of feminist theory into HCI practice, which can occur at all stages of the design process, including user research, prototyping and evaluation. However, there is still a research gap on the integration of feminism with established HCI methods. An HCI methodology that is also concerned with human values and the possible consequences of technological artifacts is Value Sensitive Design (DSV). The present work seeks to answer how to include Feminism HCI in the HCI Project with the VSD. This research took place in the context of ELLAS Project, an Open Data platform that aims to contribute to the reduction of the gender difference in STEM in Brazil, Peru and Bolivia.